Effect of Ascorbic Acid and Acetylsalicylic Acid Supplementation on Performance of Broiler Chicks Exposed to Heat Stress - Naseem, Shamoon; Younus, M.; Anwar, Bilal; Ghafoor, Aamir; Aslam, Asim; Akhter, S. (International Journal of Poultry Science, 2005)
A total of 100, day-old broiler chickens were randomly divided into 5 groups and kept under elevated temperature (34-36oC) to see the effect of ascorbic acid and acetylsalicylic acid (Sb-Asper-C, a commercial product) on the feed conversion ratio (FCR), immune status and ratio of weight of bursa, thymus and spleen to body weight. Heat stress increased the FCR but decreased the immune response and ratio of bursa, thymus and spleen to body weight of the birds. Ascorbic acid and acetylsalicylic acid supplementation during heat stress had beneficial effects on FCR, immune status and ratio of weight of bursa, thymus and spleen to body weight of the birds. Grossly, bursa thymus and spleen of heat stressed birds were atrophied but ascorbic acid and acetylsalicylic acid supplemented birds were not atrophied, No specific histopathological changes were observed in all groups.